Fantastic 4 - Gruffudd, Ioan 1973-; Alba, Jessica 1981-; Evans, Chris 1981-; Wood, Oliver 1942-2023 (Constantin Film AG, 2005)
After exposure to cosmic radiation, four astronauts become the most remarkable, if dysfunctional, superheroes of all time. Unfortunately, the mission's sponsor has also been transformed into the world's most lethal supervillain.
Original: USA 2005
Farbe, Bildformat: 2.35:1 in 16:9, DVD-9
Keywords: Film; DVD-Video